Embodied energy data implications for optimal specification of building envelopes. Issue 4 (18th May 2020) - Resalati, Shahaboddin; Kendrick, Christopher C.; Hill, Callum
ABSTRACT: Highly insulated building envelopes have become more commonplace as environmental imperatives require reduction of building carbon footprints. Whilst increased insulation levels reduce operational energy demand, the additional embodied energy investment can increase the buildings' overall environmental impact. The embodied energy consideration can determine whether, and to what extent, additional insulation is justified. The following paper investigates the impact of uncertainties of embodied energy data on the cumulative operational and embodied energy analyses and holistically appraises its implications for different stakeholders involved with the construction sector. Limitations in current life cycle assessment (LCA) calculation methods and high uncertainty of available data are recognized and reflected in the analyses through studying available environmental product declarations of various types of insulation materials and by modelling a typical semi-detached residential building in the UK as the case study. The results of such approach illustrate 'optimum insulation thicknesses' beyond which the embodied energy penalty outweighs operational energy savings. These essentially represent idealized levels of building envelope insulation that can inform the development of future standards for low energy/carbon buildings and support the adoption of LCAs as decision-making tools in informing the urgent debate of optimal insulation requirements of buildings.